Global research frontiers and thematic trends in opioid-free anesthesia over the past 20 years: a bibliometric analysis - He, Junchen; Huang, Rong; Liu, Yingzhu; Chen, Ying; Zhong, Min (Frontiers in Pharmacology, 2025)
ObjectiveOpioids have constituted an essential element of general anesthesia for a considerable length of time. However, with the increase in opioid misuse and associated postoperative adverse effects, studies related to opioid-free anesthesia (OFA) have emerged, which pose a challenge in identifying key research directions. Accordingly, the objective of this study was to provide a review of the relevant literature in the field of OFA over the past 2 decades, with the goal of identifying the prevailing trends and research Frontiers.MethodsA systematic review of the publications on OFA was conducted using the Web of Science Core Collection database, with the objective of identifying relevant publications between the years 2005 and 2024. The bibliometric analysis was conducted using CiteSpace (version 6.1. R6), VOSviewer (version 1.6.19), and R (version4.4.2).ResultsIn conclusion, 477 publications were included in this study. The number of annual publications in this field has exhibited a steady increase over the past 2 decades. The United States and its institutions were found to be the most central. Forget, Patrice, and BELOEIL H were identified as the most prolific and highly cited authors, respectively. The journal with the highest number of publications was BMC Anesthesiology. The most frequently cited journal was Anesthesia and Analgesia, followed by Anesthesiology. In addition, keyword burst, keywords co-occurrence, and analysis of cited references indicate that recent studies have focused on: opioid consumption, pain, and postoperative nausea and vomiting (PONV). Meanwhile, analysis of keyword clusters and keywords timeline view showed that the main research frontiers are sevoflurane anesthesia, plane block, multimodal anesthesia, opioid-sparing anesthesia.ConclusionOur results show that the current trends and directions of research focus on opioid consumption, pain, and PONV. Frontiers for future research are expected to include research areas related to sevoflurane anesthesia, plane block, multimodal anesthesia, opioid-sparing anesthesia.